Investigation of physiological effects of low intensity electromagnetic radiation on buckwheat - Mazets, Zhanna E.; Susha, Olga A.; Yalouskaya, Ninel A.; Kalatskaja, Joanna N.; Bonina, Tatsiana A. (Experimental Biology and Biotechnology, 2017)
A variety-specific reaction of di- and tetraploid varieties of buckwheat (Fagopyrum sagittatum gilib) on the modes of low-intensity electromagnetic radiation of the microwave range: modes 1 and 1.1 frequency 54 –74 GHz, time 20 and 12 min respectively; modes 2, 2.1 and 2.2 – frequency 62– 64 GHz and time 20, 12 and 8 min respectively was noted. It was revealed that modes with maximum (20 min) and minimum (8 min) exposure time increased the yield of electrolytes through seed’s covers relative to control in the diploid variety Kupava. The use of modes 1, 2 and 2.2 was accompanied by an increase in peroxidase activity, a decrease in germination energy, germination and a slowing down of growth processes. The electrical conductivity of the seed’s exudates of the tetraploid variety Alexandrina after 24 h of incubation decreased linearly with respect to the control in the indicated treatment variants from mode 1 to mode 2.2. Seed treatment with electromagnetic radiation modes for 12 or 8 min led to a decrease in peroxidase activity, accompanied by activation of germination and stimulation of growth processes. The received results reveal some aspects of the mechanism of electromagnetic radiation interaction with plant objects. It allows more justified use of certain modes in the cultivation of buckwheat.
Keywords: low-intensity electromagnetic radiation; buckwheat; conductivity; peroxidase; germination energy; germination; growth processes